Sprain with Foot Ulcer, Hypertension, and Obesity with Risk Factors of Eldery, Genetic Predisposition, Psychosocial Stress, and Low to Middle Economic Status - Kuntadi Syamsul Hidayat, Muhammad; Kristi, Brenda (Jurnal Ilmu Kedokteran Keluarga, 2024)
Sprain, or 'keseleo' in Indonesian, is a type of joint injury caused by tears or excessive stretching of ligaments and the joint capsule. This condition can be triggered by various risk factors. In this case, the condition was identified at a primary health care facility in Malang City. A thorough medical history was collected to identify risk factors, followed by a home visit to further detect these risk factors. This case highlights the role and application of family medicine, given the complex interplay of biopsychosocial variables that necessitates comprehensive and holistic treatment.